2012
DOI: 10.1002/jcc.22979
|View full text |Cite
|
Sign up to set email alerts
|

Simulation of multiphase systems utilizing independent force fields to control intraphase and interphase behavior

Abstract: Fixed-charge empirical force fields have been developed and widely used over the past three decades for all-atom molecular simulations. Most simulation programs providing these methods enable only one set of force field parameters to be used for the entire system. While this is generally suitable for single-phase systems, the molecular environment at the interface between two phases may be sufficiently different from the individual phases to require a different set of parameters to be used to accurately repres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
34
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 22 publications
(34 citation statements)
references
References 32 publications
0
34
0
Order By: Relevance
“…The authors compared experimental findings with their computed free energies of adsorption and qualitative behavior of peptides on different SAM surfaces such as the change in conformation upon adsorption and the orientation on the surface. This study (Collier et al 2012) demonstrated that although some FFs perform reasonably well (the best match to experiment was obtained in simulations using CHARMM22 and AMBER94 (Cornell et al 1995)), none of the FFs capture the specific interaction properties of the SAM-water interface. In particular, systematic overestimation of the binding strength of hydrophobic peptides and underestimation for negatively charged peptides was observed.…”
Section: Self-assembled Monolayer Surfacesmentioning
confidence: 82%
See 4 more Smart Citations
“…The authors compared experimental findings with their computed free energies of adsorption and qualitative behavior of peptides on different SAM surfaces such as the change in conformation upon adsorption and the orientation on the surface. This study (Collier et al 2012) demonstrated that although some FFs perform reasonably well (the best match to experiment was obtained in simulations using CHARMM22 and AMBER94 (Cornell et al 1995)), none of the FFs capture the specific interaction properties of the SAM-water interface. In particular, systematic overestimation of the binding strength of hydrophobic peptides and underestimation for negatively charged peptides was observed.…”
Section: Self-assembled Monolayer Surfacesmentioning
confidence: 82%
“…In the last decade, however, much effort has been invested to evaluate and adapt biomolecular FFs to the simulation of interfaces between biomolecules in water and specific inorganic materials, and several new approaches for developing general bio-inorganic FFs have been reported. For example, a dual-scale FF that includes two sets of partial atomic charges, optimized for each phase separately, has been developed (Biswas et al 2012). In the recently reported INTERFACE FF , partial atomic charges and van der Waals parameters have been optimized using a non-polarizable fixed-charge model for a large number of different materials based on the properties of the solid surfaces, e. g. crystal unit parameters, surface tension, water contact angle and interfacial tension, and adsorption energy of selected peptides.…”
Section: Interaction Potentialsmentioning
confidence: 99%
See 3 more Smart Citations